The Effect of Banana Fiber and Banana Peel Fiber on the Chemical and Rheological Properties of Symbiotic Yogurt Made from Camel Milk - Younes Safdari; Mohsen Vazifedoost; Zohreh Didar; Bahareh Hajirostamloo (International Journal of Food Science)
Functional foods play an important role in human health by prevention of disease. A variety of functional foods are produced around the world. Recently, the consumption of dairy products containing probiotic bacteria and prebiotics (synbiotic) has increased. Yoghurt is the most common fermented dairy product. Various compounds are used to enrich yoghurt. One of these compounds is dietary fiber. Since the peel of fruits has a significant amount of fiber and is mainly disposed of as solid waste, so using the peel of fruits to extract fiber can not only solve environmental problems but also produce a cheap and useful source that leads to the production of dietary fiber. In this study, the effect of banana fiber and banana peel fiber at different concentrations (0, 0.2, 0.5, and 1%) on the chemical and rheological properties of synbiotic yogurt prepared from camel milk was investigated. The result showed that with increase of the amount of both fibers, pH, hydration, surface tension, overall acceptability, color, and flavor of the samples decreased significantly, but the viscosity, survival of probiotic bacteria (Lactobacillus casei and Lactobacillus gasseri), and texture acceptance increased significantly (p<0.05). In conclusion, these fibers were able to reduce the syneresis of yogurt, which is one of the biggest disadvantages of yogurt, and help to increase health.